Pelatihan Digital Marketing dan Optimasi Media Sosial Untuk Meningkatkan Visibilitas UMKM - Ulya Anisatur Rosyidah; Taufiq Timur Warisaji (Journal of Community Development, 2024)
This community service activity is a collaboration between the Information Systems Study Program at Muhammadiyah University of Jember and RTIK Jember with the Sekar Kartini Jember Women's Consumer Cooperative. From the data collection carried out, it was found that many cooperative members who were MSMEs experienced marketing problems and lacked updates on digital technology. This training aims to provide training in the field of digital marketing and social media optimization to Micro, Small and Medium Enterprises (MSMEs). The main goal is to increase the visibility and competitiveness of local MSMEs in the rapidly growing digital market. The methods used in this activity include providing practical and interactive training which covers basic digital marketing concepts, social media optimization techniques, use of digital marketing tools, and online marketing strategies using effective microsites. The final result of this activity is an increase in participants' understanding and practical skills in utilizing digital platforms to promote their MSME products or services. From initial observations, only around 10% of participants knew about Digital Marketing, so at the end of the activity it increased to 90% of participants who understood the importance of Digital Marketing. In this way, it is hoped that local MSMEs can expand their market reach, increase sales and strengthen their brand awareness among local and international consumers. Apart from that, this activity is also expected to build networks and collaboration between local MSMEs, industrial players, and educational or research institutions to support local economic growth through the use of digital technology. With good collaboration, it is hoped that an ecosystem will be created that supports the growth and sustainability of MSMEs in the current digital era